2015
DOI: 10.1038/jid.2014.475
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Murine Skin Epithelium Is Crucial for Hair Follicle Morphogenesis and Epithelial–Mesenchymal Interactions

Abstract: Here, we studied how epithelial energy metabolism impacts overall skin development by selectively deleting intraepithelial mtDNA in mice by ablating a key maintenance factor (Tfam(EKO)), which induces loss of function of the electron transport chain (ETC). Quantitative (immuno)histomorphometry demonstrated that Tfam(EKO) mice showed significantly reduced hair follicle (HF) density and morphogenesis, fewer intrafollicular keratin15+ epithelial progenitor cells, increased apoptosis, and reduced proliferation. Tf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 47 publications
4
65
0
Order By: Relevance
“…These observations demonstrated that germative matrix epithelial cells at the base of the bulb of growing follicles were viable and contained abundant, metabolically active mitochondria, extending prior work showing the presence and metabolism of mitochondria by morphometry, immunohistochemistry and heat generation (Kloepper et al, 2015, Vidali et al, 2014). These measurements of mitochondrial function by multiphoton and light sheet microscopy have the advantage of much improved temporal resolution compared to protein expression, immunocytochemistry, enzyme activity and DNA content, which may persist long after cessation of the metabolism of interest.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These observations demonstrated that germative matrix epithelial cells at the base of the bulb of growing follicles were viable and contained abundant, metabolically active mitochondria, extending prior work showing the presence and metabolism of mitochondria by morphometry, immunohistochemistry and heat generation (Kloepper et al, 2015, Vidali et al, 2014). These measurements of mitochondrial function by multiphoton and light sheet microscopy have the advantage of much improved temporal resolution compared to protein expression, immunocytochemistry, enzyme activity and DNA content, which may persist long after cessation of the metabolism of interest.…”
Section: Discussionsupporting
confidence: 77%
“…Mitochondria are also important in follicle morphogenesis, since keratinocyte mitochondrial DNA depletion decreases hair follicle density, increases apoptosis and reduces proliferation. Moreover, stimulation of mitochondrial function with thyroid hormones prolongs anagen, increases follicular heat production, stimulates hair follicle keratinocyte proliferation and modifies intrafollicular keratin expression (Kloepper et al, 2015, Van Beek et al, 2008, Vidali et al, 2016, Vidali et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…in organ-cultured human skin under serum-and TH-free conditions. First, we investigated the expression of mitochondrially encoded cytochrome c oxidase I (MTCO1), the mitochondrial transcription factor A (TFAM), which controls mitochondrial biogenesis and mitochondrial DNA synthesis (Baris et al, 2011;Campbell et al, 2012;Kloepper et al, 2015;Shutt et al, 2011), and the peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), a key transcription factor that regulates mitochondrial biogenesis and numerous other cell functions including aging, whose reduction in activity has an aging-promoting effect (Dabrowska et al, 2015;Gilbert, 2013;Riera and Dillin, 2015). To assess whether any expression changes in these parameters altered also the intraepidermal mitochondrial oxidative phosphorylation, we asked whether THs modified the activity of complex I, the initial step of the mitochondrial respiratory chain (Chandel and Jeffs, 2015;Hirst, 2013;Scheffler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As regenerative organs, hair follicles offer a highly informative model to study the mechanisms of systems biology and regenerative medicine. In this article, we chose to study the hair follicle, the morphogenesis of which depends on the complex epithelial-mesenchymal interactions, as a tool to research the mechanism underlying organ regeneration [21,22]. Various studies have confirmed that hair follicles can be reconstructed by transplanting appropriate cells in vivo [913], but the mechanism behind the process is not fully clear.…”
Section: Discussionmentioning
confidence: 99%